PENERAPAN PENDEKATAN PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD N 021 BAGAN BARAT - Iyana '; Lazim.N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research up on its low usufructs student studying braze IV. SD N 021 Bagan Barat. Initially, of 22 students which reach KKM just 9 person (37,50 %). Its low causal factor result studies student because of that teacher is more tending active than student upon learning happens. So student have no chance to develop. Therefore researcher one theory which is kontekstual's learning approaching constitutes an approaching that helps to learn concern tutorial material content with real world situation. According to Trianto (2009), one class was said to apply learning approaching Contextual Teaching and Learning if applies seven components, which is (1) kontruktvisme, (2) inkuiri, (3 ) ask, (4) society study, (5) about models, (6) reflections, (7) estimations that actually. Observational form that is utilized is observational action braze. Observational job mechanism action brazes this, rendered in cycle form 2 cycles, one that each its cycle ranges 4 activities/phases, which is (1) plannings (2) performings (3) watches and (4) reflections. Activity result learns on meet i. cycle first which is 53,57% by enough categories, then increasing on appointment second becomes 64,28% get enough categories. On cycle II. appointment first increases 75,00% by good category, then on appointment second increases again 89,28% by good peer categories. Student activity result on meet i. cycle percentage first 57,14% get enough categories, then on second appointment 64,28% also get enough categories, on cycle II. first appointment 78,28% get categories well, on second Cycle appointment II. also experience step-up 92,85% by ketegori tremendously good.Key word : CTL Learning approaching, IPS Learned result.